Pengaruh Senam Terhadap Keluhan Muskuloskeletal Pada Lansia - Rina Kurnia (Poltekkes Kemenkes Surakarta, 2019)
Background: The elderly group is a high risk group that experiences various health problems, especially degenerative diseases. Elderly people tend to experience a decrease in the musculoskeletal system. Decreases in the musculoskeletal system can cause disruption to physical mobility in the elderly. Methods: The purpose of this study was to determine the effect of gymnastic on musculoskeletal disorders. The study was quantitative research with experimental one group pre-test post-test design. It was conducted at the Posyandu in Nggaren, Pandeyan Village, Ngemplak, Boyolali. Sampling was done by total sampling technique with a total of 48 respondents . Analysis of data using Wilcoxon. Results: p-value = 0.001 (p <0.005). Conclusion: there is an effect of gymnastic on musculoskeletal disorders in the elderly at the Posyandu in Nggaren, Pandeyan Village, Ngemplak, Boyolali.